The Influence of Principal Transformational Leadership, Teacher Pedagogical Competence, and School Partnership with Dudika on The Competence of State Vocational High School Graduates in Kendal District - Ana Marwani; Bunyamin; Yovitha Yuliejantiningsih (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This research is intended to investigate the influence of transformational leadership, teachers’ pedagogical competence, and school collaboration with DUDIKA on the competency of graduates from public vocational high schools in Kendal Regency. A quantitative research design was employed, and the data were collected using questionnaires. The study population consisted of all teachers working in public vocational high schools across Kendal Regency, while the sample consisted of 217 teachers selected through proportional random sampling. The data analysis was conducted through descriptive statistical techniques, assumption testing, and hypothesis examination using both simple and multiple regression methods. The findings from the multiple regression analysis reveal that transformational leadership, teachers’ pedagogical competence, and school partnerships with DUDIKA simultaneously have a positive and significant influence on graduate competency, accounting for 48.2% of the variance. Nevertheless, the simultaneous analysis also revealed a methodological limitation. Although the overall regression model was statistically significant, the individual regression coefficients for teachers’ pedagogical competence and school partnerships with DUDIKA were not statistically significant when tested together in the multivariate model. This finding suggests the possibility of multicollinearity or overlapping explanatory effects among the independent variables, which may reduce the strength of their individual contributions when analyzed simultaneously.